2013
DOI: 10.1007/s12032-013-0471-5
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening: review of benefits and harms, and recommendations for developing and low-income countries

Abstract: Breast cancer is the most common cancer in women worldwide. The disease remains a public health concern as recent evidence indicates that the breast cancer burden has increased mainly in developing and low-income countries (DLICs). Despite the demonstrated benefits, the debate about the real benefits and harms of breast cancer screening is ongoing. Many experts believe that the benefits of screening, in terms of reduced breast cancer mortality, outweigh the harms, whereas others think the opposite. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 102 publications
1
30
0
Order By: Relevance
“…In addition, there is data emerging from HICs that apparently denotes that implementation of screening mammography at the population level has led to probable overdiagnosis while only marginally reducing the rate at which women presented with advanced cancer, consequently having only a small effect on rate of death due to BC [40] . Similar evidence has been accumulated from multiple other studies [41,42] and adds to the ongoing discourse regarding the usefulness of population level BC screening using mammography [43] . Adding to the above scenario is the fact that in LMICs, BC incidence is lower and occurs more in younger age groups when breast tissue is dense.…”
Section: Status Of Mammography In Lmicssupporting
confidence: 62%
“…In addition, there is data emerging from HICs that apparently denotes that implementation of screening mammography at the population level has led to probable overdiagnosis while only marginally reducing the rate at which women presented with advanced cancer, consequently having only a small effect on rate of death due to BC [40] . Similar evidence has been accumulated from multiple other studies [41,42] and adds to the ongoing discourse regarding the usefulness of population level BC screening using mammography [43] . Adding to the above scenario is the fact that in LMICs, BC incidence is lower and occurs more in younger age groups when breast tissue is dense.…”
Section: Status Of Mammography In Lmicssupporting
confidence: 62%
“…Statistics indicate that global burden of disease (GBD) of various cancers is increasing in developing countries and this ratio is predicted to increase in the coming decades (Al-Foheidi et al, 2013). It is estimated that by 2008, 690000 out of 1380000 new cases of breast cancer are in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although universal mammography screening is the most widely adopted approach to population-based screening, comparative effectiveness research focused on different screening strategies is still important owing to the enduring debate over the value of mammography screening. While some systematic reviews have concluded that mammography screening is associated with a 20% to 25% reduction in breast cancer deaths, 1,[5][6][7][8][9][10] other reviews claim that there is no benefit 11- 17 and also express concerns that universal mammography screening leads to significant harms, specifically overdiagnosis, sometimes called overdetection of breast cancer.…”
mentioning
confidence: 99%